2019
DOI: 10.2337/db19-0043
|View full text |Cite
|
Sign up to set email alerts
|

Complement C5a Induces Renal Injury in Diabetic Kidney Disease by Disrupting Mitochondrial Metabolic Agility

Abstract: The sequelae of diabetes mellitus include microvascular complications such as diabetic kidney disease (DKD), which involves glucose-mediated renal injury that is associated with a disruption in mitochondrial metabolic agility, inflammation and fibrosis. We explored the role of the innate immune complement component C5a, a potent mediator of inflammation, in the pathogenesis of DKD in clinical and experimental diabetes. Marked systemic elevation in C5a activity was demonstrated in patients with diabetes which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 67 publications
4
67
2
Order By: Relevance
“…DKD is one of the major causes of morbidity and mortality in diabetic patients, and inappropriate activation of the complement system has been implicated in diabetes and renal diseases 24 . The plasma levels of C5a are markedly elevated in normoalbuminuric patients with diabetes compared to non‐diabetic controls 25 . In renal samples from patients with DKD, the complement system has been identified as one of the most significantly regulated pathways, 26 and activation of the complement system contributes to the progression of DKD 27 .…”
Section: Discussionmentioning
confidence: 99%
“…DKD is one of the major causes of morbidity and mortality in diabetic patients, and inappropriate activation of the complement system has been implicated in diabetes and renal diseases 24 . The plasma levels of C5a are markedly elevated in normoalbuminuric patients with diabetes compared to non‐diabetic controls 25 . In renal samples from patients with DKD, the complement system has been identified as one of the most significantly regulated pathways, 26 and activation of the complement system contributes to the progression of DKD 27 .…”
Section: Discussionmentioning
confidence: 99%
“…11,12 With chronic and diabetic kidney diseases, TCA cycle was disrupted, which may be caused by mitochondrial dysfunction. 42,43 In this study, the increased level of citrate, and aconitate in the recovered COVID-19 patients indicated their mitochondrial function may not restore to normal. Pantothenate, the precursor of coenzyme A (CoA), can slow cell injury and apoptosis and promote cell repair by increasing glutathione biosynthesis, or resistance to lipid peroxidation by forming CoA.…”
Section: Discussionmentioning
confidence: 69%
“…MASP-1 and MASP-2 levels were significantly higher in children and adults with T1DM than in their respective control groups, whereas these proteins levels decreased when glycemic control improved 57 . In a recent study it was reported that in a murine model of diabetic nephropathy, genetic knock-out or pharmacological blockade of complement component 5a receptor 1 (C5ar1) conferred renal protection and attenuated disease-associated metabolic changes, further reinforcing the importance of the complement pathway 58 .…”
Section: Discussionmentioning
confidence: 99%